Risk Disclosure in Indonesian Banking: The Role of the Board of Commissioners and Political Connections - Umi Solikhah; Bima Cinintya Pratama; Novi Dirgantari; Tiara Pandansari (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study was to examine the effect of political connections and aspects of good corporate governance, namely the frequency of meetings and the competence of the board of commissioners to risk disclosure and to consider the moderating effect of the frequency of meetings and the competence of the board of commissioners on risk disclosure. This study uses a sample of conventional banks registered with the Financial Services Authority with a sample of 41 conventional banks during the 2017–2021 period. This study uses panel data regression analysis. The techniques used in this research are descriptive statistical tests, preliminary tests (Breusch-Pagan, likelihood test, and Hausman test), diagnostic tests (Heteroscedasticity test and Autocorrelation test), and hypothesis testing. Based on the results of the three preliminary tests in determining the panel data regression model, this study uses a fixed effect model to test models 1 and 2. This study reveals that the political connection variables that use the proxy of the relationship between the members of the board of commissioners and the government (members or former members of parliament, executive, legislative and judicial institutions, leaders of political parties, and parties who are closely related to high-ranking members of the state) have a negative effect on risk disclosure. a company, because politically connected companies are less likely to disclose risk information than politically unconnected companies. The variable frequency of board of commissioners meetings has a negative effect on risk disclosure because the meetings held by the board of commissioners are less effective and there is a domination of votes from members of the board of commissioners who prioritize their personal or group interests to override the interests of the company. The competency variable of the board of commissioners has a positive effect on Risk Disclosure because the board of commissioners who have, certification, experience, and education in economics and finance can increase supervision of management in the practice of transparency of risk disclosure of a company. Meanwhile, this study can prove the role of the variable frequency of the board of commissioners meeting in weakening the negative influence of political connections on risk disclosure, while the role of the variable of competence of the board of commissioners cannot weaken the negative influence of political connections on risk disclosure.